Assessment of venous Doppler ultrasound findings of acute unilateral lower limb swelling in a tertiary facility in central Ghana: a retrospective analytical study - Emmanuel Kobina Mesi Edzie (SpringerOpen, 2021)
Abstract Background Unilateral lower limb swelling has wide differential diagnoses with varying treatment plans, requiring an early and accurate diagnosis. Doppler ultrasound offers an extensive examination of the vascular system providing a platform for diagnosis and avoidance of unnecessary invasive procedures. Thus, it becomes pertinent to ensure that all the sonographic information required for the accurate diagnosis of a swollen lower limb is documented and critically analyzed in our setting, hence this study. Results The records of a total of 151 patients with acute unilateral lower limb swelling were retrieved, females constituted the majority (51.7%). The overall mean age was 58.70 ± 16.71 years. Statistical significance was specified at p ≤ 0.05 for this study. The males were on the average 1.86 years younger than the female, but this difference was not statistically significant (p = 0.495). Patients older than 60 years constituted the majority 72 (47.7%) followed by the 40–60-year age category 61 (40.4%), and the left lower limb was affected more often 82 (54.3%). Multiple inguinal lymphadenopathy 82 (35.7%) and edema with thickened skin and subcutaneous layers 67 (29.1%) were the two most recurrent ultrasound features. There was no significant association between the sonographic features and the diagnoses made for acute unilateral lower limb swelling, except for the feature of edema with thickened skin and subcutaneous layers (p = 0.004) and the diagnosis of cellulitis (p = 0.047) that increased significantly with age. Conclusion Multiple inguinal lymphadenopathy and edema of the skin and subcutaneous layers were the most recurrent ultrasound features with cellulitis as the main diagnosis for acute unilateral lower limb swelling in our setting. Edema with thickened skin and subcutaneous layers and cellulitis both increased significantly with age. Sonographers, sonologists, and radiologists must be on the look-out for these in their practices.